Association of Lysyl Oxidase-Like 1 Gene Polymorphisms in Pseudoexfoliation Syndrome and Pseudoexfoliation Glaucoma in a Spanish Population. (2nd January 2016) - de Juan-Marcos, Lourdes; Escudero-Domínguez, Francisco A.; Hernández-Galilea, Emiliano; Cabrillo-Estévez, Lucía; Cruz-González, Fernando; Cieza-Borrella, Clara; Sánchez-Barba, Mercedes; González-Sarmiento, Rogelio
Abstract: Purpose: To evaluate the association of the lysyl oxidase-like 1 (LOXL1) single nucleotide polymorphisms (SNPs) in a Spanish population with pseudoexfoliation syndrome (XFS) and pseudoexfoliation glaucoma (XFG). Materials and methods: The present case-control study included 100 Spanish patients (60 patients with XFS and 40 patients with XFG) and 90 control subjects. Genotypes of the three single nucleotide polymorphisms of LOXL1 (rs1048661, rs3825942, and rs2165241) were analyzed with direct sequencing. Results: The G allele and the GG genotype of SNP rs3825942 were detected at a statistically higher frequency in pseudoexfoliation patients than in control subjects ( p = 3.36 × 10 −5, OR = 5.71, 95% CI: 2.30–14.18; p = 3.38 × 10 −5, OR = 6.91, 95% CI: 2.51–19.03 respectively). The T allele and the TT genotype of SNP rs2165241 presented at significantly higher frequencies in pseudoexfoliation patients than in controls ( p = 2.50 × 10 −4, OR = 2.18, 95% CI: 1.43–3.33; p = 1.21 × 10 −2, OR = 2.13, 95% CI: 1.75–3.85 respectively). No significant association between XFS/XFG and the rs1048661 was observed. The GGT haplotype composed of all three risk alleles was determined to be significantly associated with pseudoexfoliation. The genotypic and allelic distributions of the three SNPs were similar between XFS and XFG. Conclusions: This is the first study associating two SNPs of LOXL1 (rs3825942 and rs2165241) and XFS/XFG in a Spanish population, confirming findings in patients from Europe. However rs1048661 SNP did not show an association with XFS.